Implementasi Permendikbud Nomor 14 Tahun 2018 tentang Penerimaan Peserta Didik Baru Berbasis Sistem Zonasi pada Tingkat Madrasah Ibtidaiyah/Sekolah Dasar di Kecamatan Jombang - Solichin, Mujianto; Kutsi, Imama (Dirasat: Jurnal Manajemen dan Pendidikan Islam, 2019)
The new policy in â€œImplementation of New Studentsâ€ (PPDB) 2018 concerning the zoning system is implemented by the government. Student domicile with distance will be one of the considerations in PPDB. The research objective is to find out how the implementation of the Minister of Education and Cultureâ€™s policy on PPDB using the zoning system in Jombang. This study uses a qualitative method with a descriptive approach. This research shows that the implementation of the Minister of Education and Cultureâ€™s policy on zoning systems based on zoning systems at Madrasah Ibtidaiyah (Islamic Primary School) and Primary School levels in Jombang runs in accordance with the guidelines of each school due to differences in guidelines for conducting PPDB. The application of this policy has both positive and negative effects that are felt by the school and student guardians. Based on these impacts, the researcher conducted an analysis of the measurement of policy implementation and obtained the results that the implementation of the policy on the zoning system in elementary schools in Jombang went well.